Analysis Of The Effect Of Facilities And Work Motivation On Employee Performance At The Office Of The District Head Of Medan Selahang District, Medan City - Wahyuni, Nana; Waruwu, Ahmad Aswan; Batubara, Soulthan Saladin (Jurnal Fokus Manajemen, 2026)
Employee performance is a crucial factor in supporting the effectiveness of public service delivery, particularly in government institutions. Optimal performance cannot be separated from adequate work facilities and high work motivation. This study aims to analyze the effect of work facilities and work motivation on employee performance at the Medan Selayang District Office, Medan City. This research employed a quantitative method with an associative approach. The population consisted of all employees at the Medan Selayang District Office totaling 50 people, and a census technique was used as the sampling method. Data were collected through questionnaires that had been tested for validity and reliability, and then analyzed using multiple linear regression with SPSS version 27. The results showed that work facilities and work motivation partially had a positive and significant effect on employee performance. Simultaneously, work facilities and work motivation also had a significant effect on employee performance. The coefficient of determination (R²) value of 0.752 indicates that 75.2% of the variation in employee performance can be explained by work facilities and work motivation, while the remaining percentage is influenced by other factors not examined in this study. The conclusion of this study emphasizes that improving work facilities and enhancing work motivation are essential in increasing employee performance. The implications of this study are expected to serve as a reference for government institutions in formulating policies to improve employee performance and public service quality